Genotyping and pathogenicity of viral hemorrhagic septicemia virus from free-living turbot (Psetta maxima) in a Turkish coastal area of the Black Sea - Nishizawa, T; Savas, H; Isidan, H; Üstündag, C; Iwamoto, H; Yoshimizu, M (Amer Soc Microbiology, 2006)
Viral hemorrhagic septicemia (VHS) is one of the most serious fish viral diseases for cultured rainbow trout (Oncorhynchus mykiss), although VHS virus (VHSV) seems to be ubiquitous among marine fishes. In the present study, VHSV isolation was performed with free-living and cultured turbot (Psetta maxima) in the Trabzon coastal area of the Black Sea to evaluate participation of VHSV in mass mortalities of seed-produced turbot larvae. VHSV was detected in 14 of 66 free-living spawners (positive ratio, 21.2%), 1 of 65 free-living immature fish (1.5%) and 7 of 40 cultured brood stock (17.5%), respectively. Based on a partial glycoprotein gene nucleotide sequence, Turkish VHSV isolates were classified into the class I-e of genotype I and were the most closely related to the GE-1.2 isolate (> 98% identity), which was found > 20 years ago in Georgia. Thus, it was revealed that Turkish VHSV isolates were not introduced from European countries, it could be an indigenous type of VHSV distributing in the Black Sea environment. In pathogenicity tests, the Turkish isolates did not induce mortality in turbot larvae and rainbow trout fingerlings. Mass mortalities at a rate of approximately 90% occurred in turbot larvae produced by experimental seeding, although VHSV was not detected in any dead fish. Thus, it was concluded that mass mortality in the seed-produced turbot larvae was not caused by VHSV infection.
Keywords: Multiple Sequence Alignment; Wild Japanese Flounder; Scophthalmus-Maximus; Distinct Lineages; Glycoprotein Gene; Fish Rhabdovirus; European Marine; Vhsv; Susceptibility; Infection